Nuclear spin coherence properties of 151Eu3+ and 153Eu3+ in a Y2O3 transparent ceramic. (8th February 2017) - Karlsson, J; Kunkel, N; Ikesue, A; Ferrier, A; Goldner, P
Abstract: We have measured inhomogeneous linewidths and coherence times ( T 2 ) of nuclear spin transitions in a Eu 3+ :Y2 O3 transparent ceramic by an all-optical spin echo technique. The nuclear spin echo decay curves showed a strong modulation which was attributed to interaction with Y nuclei in the host. The coherence time of the 29 MHz spin transition in 151 Eu 3+ was 16 ms in a small applied magnetic field. Temperature dependent measurements showed that the coherence time was constant up to 18 K and was limited by spin-lattice relaxation for higher temperatures. Nuclear spin echoes in 153 Eu 3+ gave much weaker signals than for the case of 151 Eu 3+ . The spin coherence time for the 73 MHz spin transition in 153 Eu 3+ was estimated to 14 ms in a small magnetic field. The study shows that the spin transitions of ceramic Eu 3+ :Y2 O3 have coherence properties comparable to the best rare-earth-doped materials available.